Well-Intentioned Whiteness : Green Urban Development and Black Resistance in Kansas City - Kolavalli, Chhaya (Book collections on Project MUSE., 2023)
"This book documents how whiteness can take up space in US cities and policies through well-intentioned progressive policy agendas that support green urbanism. Through in-depth ethnographic research in Kansas City, I explore how urban food projects-a key pillar of the city's green urban policy agenda-are conceived, implemented, and how they are perceived by residents of 'food deserts,' those intended to benefit from these projects. In doing so, I examine the narratives and histories that mostly white local food advocates are guided by, and I uplift an alternative urban history of Kansas City-one that centers the contributions of Black and brown residents to urban prosperity, and highlights how displacement of communities of color, through green development, has historically been a key urban development strategy in the city. This book highlights how myopic focus on green urbanism, as a solution to myriad urban 'problems,' ends up reinforcing racial inequity, and uplifting structural whiteness. Whiteness is now oft-publicly discussed in the U.S. This makes fine-grained analysis of how whiteness takes up space in our cities even more important. I examine this process intimately, and in doing so, flesh out our understanding of how racial inequities can be (re)created by everyday urban actors"--